2017
DOI: 10.1186/s12868-017-0378-8
|View full text |Cite
|
Sign up to set email alerts
|

Sesamin protects SH-SY5Y cells against mechanical stretch injury and promoting cell survival

Abstract: BackgroundSesamin is a well-known antioxidant extracted from sesame seeds that exhibits various curative effects. The present study investigated whether sesamin would protect neuroblastoma SH-SY5Y cells against mechanical stretch injury-induced increases in reactive oxygen species (ROS) and apoptosis. Additionally, the mechanisms underlying these actives were investigated. Following exposure to mechanical stretch injury, cells were incubated for further investigations. Lactate dehydrogenase and Cell Counting K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
1
16
1
Order By: Relevance
“…It should be noticed that the neurological or cardioprotective actions caused by SSM, SesA, or other structurally similar compounds, as described previously [42,[46][47][48][49][50][51][52][53], can be intimately linked to their direct actions on the amplitude and gating of ion currents (e.g., I Na ). Similar to the ranolazine or perampanel action on I Na described previously [23,25], the inhibitory effect of SSM on ion currents seen herein may be responsible for its wide spectrum of effects observed in vivo [3,54].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It should be noticed that the neurological or cardioprotective actions caused by SSM, SesA, or other structurally similar compounds, as described previously [42,[46][47][48][49][50][51][52][53], can be intimately linked to their direct actions on the amplitude and gating of ion currents (e.g., I Na ). Similar to the ranolazine or perampanel action on I Na described previously [23,25], the inhibitory effect of SSM on ion currents seen herein may be responsible for its wide spectrum of effects observed in vivo [3,54].…”
Section: Discussionmentioning
confidence: 89%
“…For example, as the modeled cell was exposed to 1 µM SSM, the occupancy probability in the O state mildly decreased from 0.57 to 0.52, while that in the OB state resulted in a reduction from 0.079 to 0.046. to 1 μM SSM, the occupancy probability in the O state mildly decreased from 0.57 to 0.52, while that in the OB state resulted in a reduction from 0.079 to 0.046. The state diagram of a Markovian model for the NaV channel (i.e., SCN8A channel) depicted in (A) was adopted from a recent study [42]. The solutions to the ordinary differential equations in the current study were implemented in the XPP software package, and the default values for detailed numerical parameters are identical to those demonstrated previously [42], except that the values of ε (i.e., voltage-independent transition rate from the open to blocked state) and maximal conductance of INa in the control (i.e., SSM was not present) were arbitrarily assigned to be 0.3 msec −1 and 3.6 nS, respectively.…”
Section: Simulations Of Ssm-mediated Inhibition Of I Na Derived From mentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study subjected C2C12 myoblasts to different stretches (magnitudes of 5, 10, 15, and 20%), and demonstrated that 15 and 20% stretches reduced cell viability because of elevated apoptosis, whereas 5 and 10% stretches did not (Tan et al ., 2009). The present study further confirmed the contribution of ROS overproduction to HMS-induced C1C12 myoblast apoptosis by using ROS scavenger NAC, consistent with some other murine cell types such as SH-SY5Y cell and ATII cell that were rescued from stretch-induced apoptosis by inhibition of ROS (Kuhn et al ., 2017; Xu et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were seeded into BioFlex® Six-well Culture Plates (Flexcell International, Burlington, NC, USA) with collagen-coated silastic membranes at a density of 0.5 × 10 5 /cm 2 . Cells were subjected to biaxial SI with the Cell Injury Controller II instrument (Virginia Commonwealth University, Richmond, VA, USA), which released a 50-ms burst of nitrogen gas that caused a 7.5-mm downward deformation of the silastic membrane and adherent cells; this is analogous to the mechanical stress experienced by brain tissue during rotational acceleration and deceleration injury (3, 21).…”
Section: Methodsmentioning
confidence: 99%